Layer-engineered large-area exfoliation of graphene - Moon, Ji Yun; Kim, Minsoo; Kim, Seung Il; Xu, Shuigang; Choi, Jun Hui; Whang, Dongmok; Watanabe, Kenji; Taniguchi, Takashi; Park, Dong Seop; Seo, Juyeon; Cho, Sung Ho; Son, Seok Kyun; et al. (Science Advances, 2020)
The competition between quality and productivity has been a major issue for large-scale applications of two-dimensional materials (2DMs). Until now, the top-down mechanical cleavage method has guaranteed pure perfect 2DMs, but it has been considered a poor option in terms of manufacturing. Here, we present a layer-engineered exfoliation technique for graphene that not only allows us to obtain large-size graphene, up to a millimeter size, but also allows selective thickness control. A thin metal film evaporated on graphite induces tensile stress such that spalling occurs, resulting in exfoliation of graphene, where the number of exfoliated layers is adjusted by using different metal films. Detailed spectroscopy and electron transport measurement analysis greatly support our proposed spalling mechanism and fine quality of exfoliated graphene. Our layer-engineered exfoliation technique can pave the way for the development of a manufacturing-scale process for graphene and other 2DMs in electronics and optoelectronics.
Keywords: Electron transport measurements; Exfoliated graphene; Exfoliated layers; Large-scale applications; Thin metal films; Topdown; Two-dimensional materials